The pulse of energy poverty in Greece: The role of financial stress, uncertainty, and institutional resilience - Kheireddine Kheroua; Muhammad Ramzan; Kafait Ullah (Energy Policy, 2026)

Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Foliar Application of Boric Acid Modulates the Morpho-Physiological Attributes and Health Risk Factors of Turnip (Brassica rapa L.) Under Nickel Accumulation Stress - Fizza Sajid; Tahrim Ramzan; Muhammad Shahbaz; Arslan Haider; Ejaz Ahmad Waraich; Sundas Qadeer (Journal of Soil Science and Plant Nutrition, 2026)

Market connectedness and price spillovers in Ghanaian maize and yam markets: Implications for food security - Noah Larvoe; Muhammad Adzran Che Mustapa; Muhammad Ramzan; Edward Martey; José M. Gil; Zein Kallas (Food Policy, 2026)

The role of economic resilience in charting a path forward: Do supply chain pressures, energy crises, and oil market volatility threaten global sustainability? - Muhammad Ramzan; Mohammad Subhan; Shamaila Butt; José M. Gil Roig (Journal of Cleaner Production, 2026)

Exploring lateralised courtship behaviours and their influence on mating success in the yellow peach moth Conogethes punctiferalis - Muhammad Ramzan; Longfei Shi; Tianyuan Pang; Jameel M. Al-Khayri; Mustafa I. Almaghasla; Wael Elmenofy; Sherif M. El-Ganainy; Hosny H. Kesba; Ramzi Mansour; Yongjun Zhang (International Journal of Tropical Insect Science, 2026)

Dietary sodium propionate enhances growth performance, digestive enzymes, haematology and immunity in Wallago attu - Ayesha Tanveer; Noor Khan; Mahroze Fatima; Hafiz Abdullah Shakir; Ayesha Khizar; Syed Zakir Hussain Shah; Laiba Kareem; Saba Aftab; Malik Muhammad Ramzan; Ahmed Mustafa; Simon John Davies (Journal of Fish Biology, 2026)
Sodium propionate (SP), a short‐chain fatty acid, has been widely used as a feed additive to improve fish growth and health status. The current experiment was designed to investigate the effects of dietary SP on growth, enzymatic activities, haematology and immune status of Wallago attu . Fingerlings (initial weight = 8.80 ± 0.58 g) were fed with graded levels of SP comprising 0.0, 0.5, 1.0, 2.0, 4.0 and 8.0 g/kg levels for 60 days in triplicate glass aquaria (89 × 58 × 61 cm [length × width × depth]). The results showed significant ( p W. attu fingerlings when fed with graded levels of SP. In conclusion, the SP supplementation in W. attu showed best results ranged between 2 and 4 g/kg level by improving fish health and growth performance.

Impact of CODMn gradients on element cycling in a membrane-aeration combined with bacteria–algae symbiosis system for mariculture wastewater treatment - Yingzhen Wei; Muhammad Naeem Ramzan; Wen Yang; Zhongming Zheng (Journal of Environmental Chemical Engineering, 2026)

Thiourea Mediated Improvement of Drought Stress in Maize (Zea Mays L.): Unrevealing Morpho-Physiological, Biochemical, and Root Attributes - Arslan Haider; Ejaz Ahmad Waraich; Surriya Bibi; Tahrim Ramzan; Muhammad Ahmad; Muhammad Faisal Maqsood (Journal of Soil Science and Plant Nutrition, 2026)

Mechanistic Insights into Silicon-Induced Modulation of Morphophysiological Traits and Plant Defense System in Mung Bean (Vigna Radiata L.) under Drought Stress - Mazhar Abbas; Ejaz Ahmad Waraich; Muhammad Ahmad; Nazia Ishfaq; Arslan Haider; Tahrim Ramzan; Muhammad Nazim; Usman Zulfiqar; Muhammad Faisal Maqsood; Abdul Rehman; Waleed A. A. Alsakkaf; Hayssam M. Ali (Journal of Soil Science and Plant Nutrition, 2026)

Leveraging Extremophyte Adaptations as a Roadmap for Crop Design for Arid Lands - Mohsin Tanveer; Lei Wang; Hamza Tariq; Muhammad Talha Ramzan; Alisdair R. Fernie; Jaume Flexas; Sergey Shabala; Josep Peñuelas (Global Change Biology, 2026)
Anthropogenic climate change is driving a convergence of rapid soil aridification and secondary salinization that threatens to degrade over half of the world's arable land. As conventional glycophytic crops reach their physiological limits, global food security depends on decoding the evolutionary adaptations of extremophytes. This review synthesizes the functional traits and ecosystem‐level impacts of extremophytes, the native flora of these marginal environments, and evaluates their potential as a biophysical buffer against land degradation. Here, we identify two cornerstone strategies that allow these plants to thrive where others fail: (i) the precise spatiotemporal orchestration of reactive oxygen species (ROS) as critical signaling molecules for developmental plasticity; and (ii) the active recruitment of stress‐protective microbiomes via targeted exudation, effectively transforming barren soil into a functional ecosystem. We argue that integrating extremophytes into diversified agroecosystems, through intercropping, phytoremediation rotations, and circular bioeconomy models, offers quantifiable results to enhance ecosystem multifunctionality and sustainably intensify production on degrading lands. By bridging profound mechanistic discovery with ecological engineering, this perspective provides an actionable plan for translating extremophyte biology into crops capable of withstanding a drier future.

Analyzing the synergies between green energy, green technology, and environmental sustainability in China: Novel insights from time-varying quantile approaches - Shamaila Butt; Muhammad Ramzan; Muhammad Ali Chohan; Natasha Murtaza; Tomiwa Sunday Adebayo (Gondwana Research, 2026)

Foliar Application of Melatonin and Ascorbic Acid Mitigates Salinity Stress by Improving the Morpho-Physiological, and Antioxidant Defense System in Canola (Brassica Napus L.) - Tahrim Ramzan; Muhammad Shahbaz; Farooq Ahmad; Ejaz Ahmad Waraich (Journal of Soil Science and Plant Nutrition, 2026)

Assessing the Efficacy of Exogenous Application of Glycine Betaine in Canola (brassica napus l.) Under Nickel Stress - Aneeza Muzafar; Muhammad Shahbaz; Tahrim Ramzan; Arslan Haider; Maha Fatima (Journal of Soil Science and Plant Nutrition, 2026)

Growth and Phytostabilization Potential of Willow under Rare Earth Elements Exposure in Floating Treatment Wetlands - Muhammad Mohsin; Muhammad Ramzan; Edita Baltrėnaitė-Gedienė; Nicole Nawrot; Erik Kaipiainen; Fahad Rasheed; Zikria Zafar; Ewa Wojciechowska; Ari Pappinen; Suvi Kuittinen (Water, Air, & Soil Pollution, 2026)
Phytoremediation of contaminated freshwater bodies with rare earth elements (REEs) is a promising nature-based solution, but it is rarely studied. Here, we studied how efficiently willow ( Salix schwerinii: SS ) and cultivar (Klara: KL) purify water and react to three combined doses of REEs. SS and KL were subjected to increasing combined doses of REEs, specifically lanthanum (La) and neodymium (Nd), for 8 weeks in floating treatment wetlands (FTWs). The treatments included: T0 (tap water without REEs), T1 (10 µM La + 10 µM Nd), T2 (20 µM La + 20 µM Nd), and T3 (40 µM La + 40 µM Nd). The study aimed to evaluate how La and Nd affect willow growth, including height, dry biomass, and tolerance index, as well as their uptake and translocation within the roots, stems and leaves. Results showed that willow height increased over time, with significant biomass development and a noticeable allocation to stem biomass under REEs exposure. Height and biomass tolerance indices indicated that SS and KL exhibited high tolerance to REEs. The findings revealed the highest accumulation of La (25,252 μg plant −1 ) and Nd (18,252 μg plant −1 ) in the roots of SS in treatment T3. KL also showed the highest accumulation of La (16,153 μg plant −1 ) and Nd (13,209 μg plant −1 ) in roots, but in treatment T2. Moreover, SS and KL demonstrated increased translocation of La and Nd, particularly from the water solution to the roots, with minimal translocation to the leaves and stems. In SS, La and Nd removal efficiencies ranged from 56–95% and 40–74%, respectively. For KL, La removal varied from 22–90%, while Nd removal ranged from 21–68%. A considerable accumulation of nutrients such as P, K, Mg, and Ca in the willow tissues was also observed. Further research is needed to evaluate the long-term removal and recovery of REEs by willow and other perennial plants, with a primary focus on environmental factors and design of FTWs which may influence the uptake and translocation of REEs in plants.

Bentonite clay in aflatoxin mitigation: advances, efficiency and perspectives - Syed Ali Raza Naqvi; Muhammad Kaleem Khan Khosa; Ameer Fawad Zahoor; Matloob Ahmad; Ariba Abdullah; Muhammad Ramzan Saeed Ashraf Janjua; Syed Ansar Abidi; Fatma Mohamed Ameen Khalil; Mohamed Fawzy Ramadan; João Miguel Rocha (Archives of Microbiology, 2026)

Bacterial community of the shrimp (Litopenaeus vannamei) gut and its relationship with water quality in a recirculating aquaculture system (RAS) - Arslan Emmanuel; Bilal Raza; Muhammad Naeem Ramzan; Zhongming Zheng (Aquaculture International, 2025)

Water level forecasting in coastal cities using a hybrid deep learning approach - Abdur Rahman; M. Hafidz Omar; Tahir Mahmood; Nasir Abbas; Muhammad Riaz; Naeem Ramzan (Science of The Total Environment, 2025)

Emission characteristics of a compression ignition engine using biodiesel and clove oil antioxidant blends - Sher Muhammad Ghotto; Sajjad Bhangwar; Ramez Raja; Muhammad Kashif Abbasi; Gordhan Das Valasai; Muhammad Ramzan Luhur; Stefano Landini (Biomass and Bioenergy, 2025)

Development of a Novel Composite Catalyst containing Renewable Biochar blended with Zinc Oxide and Copper Diphenyl Amine for Visible Light Photocatalytic Degradation of Methylene Blue - Muhammad Raashid; Muhammad Zain Akram; Mohsin Kazmi; Kashaf Imran; Amir Ikhlaq; Muhammad Bin Saeed; Naveed Ramzan; Zafar Masood (Water, Air, & Soil Pollution, 2025)

Fitness, oviposition preference and larval attraction of yellow peach moth Conogethes punctiferalis on sweet and waxy corn cultivated in China - Muhammad Ramzan; Longfei Shi; Huaijing Liu; Aishah Alatawi; Yan Xiong; Yue Wang; Ifra Kainat; Ramzi Mansour; Yongjun Zhang (Phytoparasitica, 2025)

Analyzing the double-chain deoxyribonucleic acid model: bifurcation, chaos, and sensitivity insights through advanced analytical techniques - Sadique Rehman; Aamir Farooq; H. W. A. Riaz; Kamran Ullah Khan; Majid Hussain Shah; Muhammad Ramzan (Theory in Biosciences, 2025)

Efficacy and Safety of Mesenchymal Stromal Cells for Steroid-Refractory Acute Graft-versus-Host Disease: An Updated Meta-Analysis of Randomized Controlled Trials - Iftikhar Khan; Umama Rehman; Fatima Aslam; Saad Khan; Umna Bhatti; Hussain Ramzan; Fatima Naveed; Javeria Nawaz; Syeda Malaika Raza; Kiran Inam; Faiza Rajput; Syed Muhammad Seyab; et al. (Stem Cell Reviews and Reports, 2025)

Unraveling the potential of zinc oxide nanoparticles on alleviating arsenic toxicity in wheat (Triticum aestivum L.) varieties: a comparative assessment of histology and phenomics - Eimaan Aamer; Muhammad Saeed; Faroha Liaqat; Muhammad Ramzan Khan; Muhammad Kashif Naeem; Ghazala Mustafa; Riffat Naseem Malik (Physiology and Molecular Biology of Plants, 2025)

Shaping a greener future: the moderating role of financial development on political stability in evaluating environmental sustainability across ASEAN economies - Shamaila Butt; Muhammad Ramzan; Muhammad Ali Chohan; Muddassar Bilal; Umbrin Akbar (Clean Technologies and Environmental Policy, 2025)

Retraction notice to “Comparative study of ozonation and ozonation catalyzed by Fe-loaded biochar as catalyst to remove methylene blue from aqueous solution” [Chemosphere 307 Part 1, November 2022, 135738] - Muhammad Babar; Hafiz Muhammad Shahzad Munir; Aamna Nawaz; Naveed Ramzan; Umair Azhar; Muhammad Sagir; Muhammad Suleman Tahir; Amir Ikhlaq; Siti Nuurul huda Mohammad Azmin; Muhammad Mubashir; Kuan Shiong Khoo; Kit Wayne Chew (Chemosphere, 2025)

Host preference and fitness parameters of an invasive leaf eating caterpillar Trilocha varians (Lepidoptera: Bombycidae): implications for ornamental plant pest management - Noura J. Alotaibi; Zhuo Zhihang; Sajida Mushtaq; Sadia Maalik; Muhammad Ramzan; Waqar Majeed; Habib Ali; Xu Danping; Ammara Riaz (International Journal of Tropical Insect Science, 2025)

Digital economy and export complexity: unveiling its role in transforming china’s manufacturing industry - Guo Qingran; Ummara Razi; Muhammad Ramzan; Ding Cuicui; László Vasa (Environment, Development and Sustainability, 2025)

Boosted wound healing and anticancer potential of polymer functionalized cerium oxide nanomaterials - Muhammad Khawar Abbas; Yasir Javed; Naveed Akhtar Shad; Azhar Rasul; Amna Bashir; Syed Fazil Bin Farukh; Heba Taha Abdulghani; Wasim Abbas; Aisha Sethi; Muhammad Ramzan Khawar; Dongwhi Choi (Journal of Trace Elements in Medicine and Biology, 2025)

Therapeutic applications of quercetin-metallic complexes: a review - Nasreen Ramzan; Huma butt; Muhammad Azeem; Muhammad Hanif; Khalid Mahmood; Sadia Rehman; Dure shahwar; Muhammad Zeeshan; Qurat-ul-Ain Ahmad; Mehreen Jabeen (BioMetals, 2025)

The compound Bacillus and sea purslane (Sesuvium portulacastrum) enhanced aquaculture wastewater treatment efficiency: Insights from a study on microbial community distributions - Hongmei Yuan; Junxian Li; Haihang Wang; Regan Nicholaus; Muhammad Naeem Ramzan; Wen Yang; Zhongming Zheng; Yangcai Wang (Aquaculture, 2025)

Interconnectedness among green energy, technology, geopolitical risk, and environment in Asia: The mitigating role of monetary freedom - Muhammad Ramzan; Shamaila Butt; Muhammad Ali Chohan; Muhammad Farrukh Shahzad (Journal of Cleaner Production, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

Manipulating electron shuttling in photo fermentative biohydrogen production from lignocellulosic biomass through engineered Z-scheme photo nanocatalysts - Muhammad Usman; Faiqa Nadeem; Farzana Jabeen; Muneeb Ur Rahman; Hina Ramzan; Muhammad Shahzaib; Zhiping Zhang; Nadeem Tahir (Chemical Engineering Journal, 2025)

Performance and Microbial Community Analysis of Integrated Bioremediation Systems with Photosynthetic Bacteria in Treating Mariculture Tailwater - Muhammad Naeem Ramzan; Ding Shen; Yingzhen Wei; Arslan Emmanuel; Wen Yang; Jinyong Zhu; Yangcai Wang; Zhongming Zheng (Journal of Ocean University of China, 2025)

A review: Improving aquaculture rearing water quality by removal of nutrients using microalgae, challenges and future prospects - Bilal Raza; Muhammad Naeem Ramzan; Wen Yang (Aquaculture, 2025)

Enhanced charge transferring through defects-mediated metal‑carbon nanocomposites for efficient dye degradation under visible light - Muneeb Ur Rahman; Faiqa Nadeem; Muhammad Usman; Muhammad Shahzaib; Hina Ramzan; Nimra Nadeem; Zhiping Zhang; Nadeem Tahir (Journal of Water Process Engineering, 2025)

Integrating the modified amphiphilic Eleocharis tuberosa starch to stabilize curcuminoid-enriched Pickering emulsions for enhanced bioavailability, thermal stability, and retention of the hydrophobic bioactive compound - Zafarullah Muhammad; Rabia Ramzan; Abdullah; Hafiz Muhammad Khalid Abbas; Wu Sun; Guoqiang Zhang (Carbohydrate Polymers, 2025)

Dynamic linkages and spillover effects of biodiversity risk in socially responsible investment and commodity markets - Muhammad Ramzan Kalhoro; Khalid Ahmed (Journal of Environmental Management, 2025)

Catalytic-assisted remediation and phytotoxicity evaluations of organic pollutants in the presence of metal-doped Bi2O3-based NPs catalyst - Farah Fahim; Muhammad Imran; Muhammad Ramzan; Zarish Nazeer; Awais Ali; Haﬁz M.N. Iqbal (Journal of Environmental Management, 2025)

Nitrogen and phosphorus-related functional genes enhance nutrient removal in the integrated aquaculture wastewater bioremediation system in the presence of photosynthetic bacteria - Muhammad Naeem Ramzan; Ding Shen; Yingzhen Wei; Arslan Emmanuel; Regan Nicholaus; Wen Yang; Zhongming Zheng (Aquaculture International, 2025)

The comparative transcriptome analysis of two green super rice genotypes with varying tolerance to salt stress - Nageen Zahra; Muhammad Uzair; Imdad Ullah Zaid; Kotb A. Attia; Safeena Inam; Sajid Fiaz; Rizk M. Abdallah; Muhammad Kashif Naeem; Umer Farooq; Nazia Rehman; Ghulam Muhammad Ali; Jianlong Xu; et al. (Molecular Biology Reports, 2024)

Achieving carbon neutrality through digital infrastructure and public debt - Qamar Abbas; Yao HongXing; Muhammad Ramzan; Sumbal Fatima (Clean Technologies and Environmental Policy, 2024)

Polygonum bistorta Linn. as a green source for synthesis of biocompatible selenium nanoparticles with potent antimicrobial and antioxidant properties - Hafiz Abdul Haseeb; Muhammad Aslam Khan; Hassam Rasheed; Muhammad Usman Zahid; Thu Dung Doan; Muhammad Aamir Ramzan Siddique; Uzair Ahmad; Syed Ali Imran Bokhari (BioMetals, 2024)

Comparative genomics and evolutionary analysis of dengue virus strains circulating in Pakistan - Aziz Ul-Rahman; Muhammad Zubair Shabbir; Majeeda Rasheed; Nusrat Shafi; Kalsoom AbdulRazaq; Hamna Ramzan; Rauf Mehmood; Junaid Ali Khan (Virus Genes, 2024)

Price bubbles and Co-bubbles in the green economy market - Marcin Potrykus; Imran Ramzan; Muhammad Mazhar; Elie Bouri (Journal of Environmental Management, 2024)

A fluid approach to cosmic-ray modified shocks - B. Ramzan; S.N.A. Qazi; Irshad Salarzai; Muhammad Tahir; Arshad M. Mirza; A. Rasheed; M. Jamil (Advances in Space Research, 2024)

The impact of energy (Electricity) losses on load capacity factor: A dynamic ARDL-based evidence from Pakistan - Shinan Zhao; Sharafat Ali; Muhammad Asghar; Muhammad Ramzan Sheikh; Sami Ullah (Process Safety and Environmental Protection, 2024)

Modulating glucose metabolism and relieving hypoxia for enhanced Chemo/Photoimmunotherapy with photosensitizing enzymatic nanodrugs - Zhiyuan Zheng; Shan Lu; Yue Wu; Ayşe Başak Kayitmazer; Ayyaz Ahmad; Naveed Ramzan; Muhammad Shahid Rafique; Jintao Yang; Xiaolong Zhou; Yisheng Xu; Yi Si (Chemical Engineering Journal, 2024)

Total factor productivity and environmental quality: measuring the role of financial stability in BRICS countries - Qamar Abbas; Yao HongXing; Muhammad Ramzan; Sumbal Fatima (Environment, Development and Sustainability, 2024)

Appraisal of potentially toxic metals contamination in protein supplements for muscle growth: A chemometric approach and associated human health risks - Misbah Irshad; Mahmood Ahmed; Muhammad Ramzan; Mehreen Fatima; Fatima Aftab; Mudassar Sanaullah; Shaista Qamar; Zohaib Iftikhar; Tanveer A. Wani; Seema Zargar (Journal of Trace Elements in Medicine and Biology, 2024)

Do financial inclusion, inclusive digitalization and growth promote clean energy portfolio? - Muhammad Ramzan; Yao HongXing; Qamar Abbas; Sumbal Fatima (Clean Technologies and Environmental Policy, 2024)

Retraction Note: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2024)

Transcriptomics of developing grains reveals putative candidate genes for grain zinc and iron in bread wheat cultivar Zincol-2016 - Samar Naseer; Mengjing Sun; Bushra Bibi; Humaira Qayyum; Muhammad Ramzan Khan; Chenyang Hao; Xueyong Zhang; Yuanfeng Hao; Awais Rasheed; Zhonghu He (Journal of Cereal Science, 2024)

Carbon reduction through renewable energy and digitalization in emerging economies: Moderating role of public debt - Qamar Abbas; Yao HongXing; Muhammad Ramzan; Sumbal Fatima (Environmental Science and Pollution Research, 2024)

Identification of provenance of Basmati rice grown in different regions of Punjab through multivariate analysis - Muhammad Saifullah; Awais Nisar; Ramzan Akhtar; Syed M. Husnain; Shamila Imtiaz; Bashir Ahmad; Munib Ahmed Shafique; Saira Butt; Muhammad Arif; Abid Majeed Satti; Muhammad Shahzad Ahmed; Simon D. Kelly; et al. (Food Chemistry, 2024)

Morphological, phenotypic and nutritional characterization of exotic and local tomato germplasm under tunnel - Fozia; Anam Zahid; Yike Gao; Muhammad Ramzan; Mohamed A.A. Ahmed; Piotr Stępień; Ahmed F. Yousef (Food Bioscience, 2024)

Salicylic Acid-Induced Antioxidant Defense System Alleviates Cadmium Toxicity in Wheat - Umer Hayat; Kaleem ul din; Arslan Haider; Tahrim Ramzan; Bilal Ahmad Shahzad; Muhammad Ahmad; Usman Zulfiqar; Muhammad Faisal Maqsood; Sadam Hussain; Mona S. Alwahibi; Mohamed S. Elshikh (Journal of Soil Science and Plant Nutrition, 2024)

Treatment of marble industry wastewater by Brassica napus (L.) under oxalic acid amendment: efficacy as fodder and carcinogenic risk assessment - Arwa Abdulkreem AL-Huqail; Ibtisam Mohammed Alsudays; Suliman Mohammed Suliman Alghanem; Ramzan Anwar; Mujahid Farid; Wajiha Sarfraz; Muhammad Zubair; Zaki Ul Zaman Asam; Mohsin Abbas; Muhammad Rizwan (Environmental Science and Pollution Research, 2024)

Metallic minerals production and environmental sustainability in China: Insights using ARDL bounds testing and wavelet coherence approaches - Qamar Abbas; Yao Hongxing; Muhammad Shahbaz; Muhammad Ramzan; Sumbal Fatima (Resources Policy, 2024)

Green synthesis of ZnO nanocubes from Ceropegia omissa H. Huber extract for photocatalytic degradation of bisphenol An under visible light to mitigate water pollution - Awais Ahmad; Muhammad Ramzan Khawar; Ikram Ahmad; Muhammad Hassan Javed; Anees Ahmad; Abdul Rauf; Umer Younas; Arif Nazir; Dongwhi Choi; Abdulnasser M. Karami (Environmental Research, 2024)

Phytoremediation of heavy metal-contaminated soil of Lyari River using bioenergy crops - Musarrat Ramzan; Saira Sarwar; Muhammad Zaheer Ahmad; Rifat Zubair Ahmed; Tanveer Hussain; Iqtidar Hussain (South African Journal of Botany, 2024)

Investigating the quantum size effects of multi-walled carbon nanotubes (MWCNTs) in photocatalytic fermentative biohydrogen production - Hina Ramzan; Faiqa Nadeem; Muhammad Usman; Muhammad Shahzaib; Muneeb Ur Rahman; Fuhua Shen; Zhiping Zhang; Reeta Rani Singhania; Farzana Jabeen; Waheed Afzal; Nadeem Tahir (Journal of Cleaner Production, 2024)

An experimental study on early age compression and shear strength properties of mixed clay soil - Azhar Abbas; Muhammad Akbar; Pan Huali; Ali Zar; Samar Ramzan; Zahoor Hussain (Arabian Journal of Geosciences, 2024)

Role of nuclear energy, geothermal energy, agriculture, and urbanization in environmental stewardship - Muhammad Ramzan; Ummara Razi; Muhammad Usman; Suleman Sarwar; Amogh Talan; Hardeep Singh Mundi (Gondwana Research, 2024)

BRICS and the climate challenge: navigating the role of factor productivity and institutional quality in CO2 emissions - Qamar Abbas; Yao HongXing; Muhammad Ramzan; Sumbal Fatima (Environmental Science and Pollution Research, 2023)

Seaweed Application Enhanced the Growth and Yield of Pea (Pisum sativum L.) by Altering Physiological Indices - Safina Naz; Hafiza Muniba Din Muhammad; Muhammad Ramzan; Bushra Sadiq; Riaz Ahmad; Saqib Ali; Abdulaziz Abdullah Alsahli; Muhammad Ahsan Altaf (Journal of Soil Science and Plant Nutrition, 2023)

An analytical framework to link factors affecting agricultural trade intensity in the world: pathways to sustainable agricultural development 2030 agenda - Muhammad Ramzan; Hong Li (Environment, Development and Sustainability, 2023)

Depolymerization of lignin: Recent progress towards value-added chemicals and biohydrogen production - Hina Ramzan; Muhammad Usman; Faiqa Nadeem; Muhammad Shahzaib; Muneeb Ur Rahman; Reeta Rani Singhania; Farzana Jabeen; Anil Kumar Patel; Chunyao Qing; Shengyong Liu; Grzegorz Piechota; Nadeem Tahir (Bioresource Technology, 2023)

Triggering photo fermentative biohydrogen production through NiFe2O4 photo nanocatalysts with various excitation sources - Shengyong Liu; Fuhua Shen; Faiqa Nadeem; Muneeb Ur Rahman; Muhammad Usman; Hina Ramzan; Muhammad Shahzaib; Reeta Rani Singhania; Wang Yi; Chunyao Qing; Nadeem Tahir (Bioresource Technology, 2023)

A panacea to address the legal, administrative and economic aspects of space debris - Abbas Sheer; Sidra Fatima; Mohammad Owais Farooqui; Muhammad Ramzan Kasuri (Advances in Space Research, 2023)

Moderating role of green innovation and fiscal expenditure towards achieving the Sustainable Development Agenda 2030 at provincial-level in China: policy implication from green total factor productivity - Yongzhong Jiang; Muhammad Ramzan; Abraham Ayobamiji Awosusi; Tomiwa Sunday Adebayo (Environmental Science and Pollution Research, 2023)

Adsorptive and photocatalytic degradation potential of porous polymeric materials for removal of pesticides, pharmaceuticals, and dyes-based emerging contaminants from water - Azeem Intisar; Arooj Ramzan; Shahzar Hafeez; Nazim Hussain; Muhammad Irfan; Nasir Shakeel; Komal Aziz Gill; Amjad Iqbal; Marcin Janczarek; Teofil Jesionowski (Chemosphere, 2023)

Do coal efficiency, climate policy uncertainty and green energy consumption promote environmental sustainability in the United States? An application of novel wavelet tools - Xuan Liu; Tomiwa Sunday Adebayo; Muhammad Ramzan; Sami Ullah; Shujaat Abbas; Victoria Olushola Olanrewaju (Journal of Cleaner Production, 2023)

Comprehensive insights into the regulatory mechanisms of lncRNA in alkaline-salt stress tolerance in rice - Obaid Ur Rehman; Muhammad Uzair; Muhammad Shahbaz Farooq; Bilal Saleem; Safira Attacha; Kotb A. Attia; Umer Farooq; Sajid Fiaz; Wael. H. El-Kallawy; Itoh Kimiko; Muhammad Ramzan Khan (Molecular Biology Reports, 2023)

Lipoic Acid Positively Regulates Tomato Growth and Yield by Improving Organic Osmolytes and Antioxidant Defense System Under Saline Conditions - Rohina Bashir; Hafiza Naila Ramzan; Saqib Mahmood; Muhammad Awais; Samina Hassan; Muhammad Aqeel; Haifa A. S. Alhaithloul; Tasahil S. Albishi; Sameer H. Qari; Ali Noman (Journal of Soil Science and Plant Nutrition, 2023)

Exploring the relationships between attitudes toward emission trading schemes, artificial intelligence, climate entrepreneurship, and sustainable performance - Bin Hu; Shoaib Asim; Muhammad Sibt-e-Ali; Muhammad Qasim Javaid; Muhammad Ramzan (Environmental Science and Pollution Research, 2023)

Major challenges in widespread adaptation of aerobic rice system and potential opportunities for future sustainability - Muhammad Shahbaz Farooq; Hira Fatima; Obaid Ur Rehman; Muhammad Yousuf; Rabia Kalsoom; Sajid Fiaz; Muhammad Ramzan Khan; Muhammad Uzair; Shuhao Huo (South African Journal of Botany, 2023)

Advances in the catalyzed photo-fermentative biohydrogen production through photo nanocatalysts with the potential of selectivity, and customization - Faiqa Nadeem; Huan Zhang; Nadeem Tahir; Zhiping Zhang; Reeta Rani Singhania; Muhammad Shahzaib; Hina Ramzan; Muhammad Usman; Muneeb Ur Rahman; Quanguo Zhang (Bioresource Technology, 2023)

Exogenous Application of Melatonin Improves the Growth and Productivity of Two Broccoli (Brassica oleracea L.) Cultivars Under Salt Stress - Hasan Sardar; Muhammad Arif Ramzan; Safina Naz; Sajid Ali; Shaghef Ejaz; Riaz Ahmad; Muhammad Ahsan Altaf (Journal of Plant Growth Regulation, 2023)

Morphological and molecular observations of nematodes belonging to the family Hoplolaimidae from the Thar Desert, Pakistan - Ramzan Ali; Ebrahim Shokoohi; Erum Iqbal; Muhammad Ismail Bhatti; Saboohi Raza (Biologia, 2023)

Does clean energy matter? The dynamic effects of different strategies of renewable energy, carbon emissions, and trade openness on sustainable economic growth - Jianrun Wang; Muhammad Ramzan; Fauzia Makin; Ch Kamran Mahmood; Carlos Samuel Ramos-Meza; Vipin Jain; Malik Shahzad Shabbir (Environment, Development and Sustainability, 2023)

Cellular and Non-cellular Antioxidant Properties of Vitamin E–Loaded Metallic-Quercetin/Polycaprolactone Nanoparticles for the Treatment of Melanogenesis - Nasreen Ramzan; Muhammad Azeem; Khalid Mahmood; Shahid Shah; Fazal Rahman Sajid Chughtai; Muhammad Hanif; Nabeela Ameer; Zakia Bashir; Farhan Siddique; Muhammad Qaisar (AAPS PharmSciTech, 2023)

Supplementation of Moringa based zinc oxide nanoparticles mitigates salt stress in Celosia argentea through reduced chloride (Cl −) uptake and modulation in physiochemical attributes - Musarrat Ramzan; Nabeera Naveed; Muhammad Zaheer Ahmed; Hina Ashraf; Anis Ali Shah; Muhammad Jamil; Zahoor Ahmad; Ryan Casini; Hosam O. Elansary (South African Journal of Botany, 2023)

Exogenous application of glutathione and gamma amino-butyric acid alleviates salt stress through improvement in antioxidative defense system and modulation of CaXTHs stress-related genes - Musarrat Ramzan; Anis Ali Shah; Muhammad Zaheer Ahmed; Muhammad Adnan Bukhari; Liaqat Ali; Ryan Casini; Hosam O. Elansary (South African Journal of Botany, 2023)

A step towards achieving SDG 2030 agenda: Analyzing the predictive power of information globalization amidst technological innovation-environmental stewardship nexus in the greenest economies - Muhammad Ramzan; Sami Ullah; Syed Ali Raza; Muhammad Nadeem (Journal of Environmental Management, 2023)

Corrigendum to “The effects of environmental degradation on agriculture: Evidence from European countries” [Gondwana Res. 106 (2022) 92–104] - Duojiao Tan; Festus Fatai Adedoyin; Rafael Alvarado; Muhammad Ramzan; Md Safiullah Kayesh; Muhammad Ibrahim Shah (Gondwana Research, 2023)

Machine Learning and Artificial Neural Networks-Based Approach to Model and Optimize Ethyl Methanesulfonate and Sodium Azide Induced In Vitro Regeneration and Morphogenic Traits of Water Hyssops (Bacopa monnieri L.) - Kubra Mirza; Muhammad Aasim; Ramzan Katırcı; Mehmet Karataş; Seyid Amjad Ali (Journal of Plant Growth Regulation, 2023)

Environmental sustainability in Vietnam: evaluating the criticality of economic globalisation, renewable energy, and natural resources - Abraham Ayobamiji Awosusi; Huseyin Ozdeser; Opeoluwa Seun Ojekemi; Ibrahim Adeshola; Muhammad Ramzan (Environmental Science and Pollution Research, 2023)

Greenfield investments, economic complexity, and financial inclusion-environmental quality nexus in BRICS Countries: Does renewable energy transition matter? - Ayoub Zeraibi; Atif Jahanger; Tomiwa Sunday Adebayo; Muhammad Ramzan; Yang Yu (Gondwana Research, 2023)

Spatial disparities in household expenditure on safe drinking water in Pakistan: An application of geographically weighted regression - Sami Ullah Khan; Muhammad Ramzan Sheikh (Groundwater for Sustainable Development, 2023)

Analyzing the role of green innovation and public-private partnerships in achieving sustainable development goals: a novel policy framework - Liu Ning; Kashif Raza Abbasi; Khadim Hussain; Rafael Alvarado; Muhammad Ramzan (Environmental Science and Pollution Research, 2023)

Triticum aestivum: antioxidant gene profiling and morpho-physiological studies under salt stress - Musarrat Ramzan; Memoona Gillani; Anis Ali Shah; Adnan Noor Shah; Naheed Kauser; Muhammad Jamil; Rana Touqeer Ahmad; Sami Ullah (Molecular Biology Reports, 2023)

CRISPR/Cas9 editing of wheat Ppd-1 gene homoeologs alters spike architecture and grain morphometric traits - Aliya Errum; Nazia Rehman; Muhammad Uzair; Safeena Inam; Ghulam Muhammad Ali; Muhammad Ramzan Khan (Functional & Integrative Genomics, 2023)

Environmental perspectives on the impacts of trade and natural resources on renewable energy utilization in Sub-Sahara Africa: Accounting for FDI, income, and urbanization trends - Liu Dingru; Stephen Taiwo Onifade; Muhammad Ramzan; Mamdouh Abdulaziz Saleh AL-Faryan (Resources Policy, 2023)

Functionalized graphene oxide-zinc oxide hybrid material and its deployment for adsorptive removal of levofloxacin from aqueous media - Nimra Ismail; Muhammad Imran; Muhammad Ramzan; Ayesha Anwar; Ibrahim A. Alsafari; Muhammad Asgher; Hafiz M.N. Iqbal (Environmental Research, 2023)

Success of Aquaculture Industry with New Insights of Using Insects as Feed: A Review - Amna Hameed; Waqar Majeed; Muhammad Naveed; Uzma Ramzan; Matteo Bordiga; Maryam Hameed; Saud Ur Rehman; Naureen Rana (Fishes, 2022)
Most of world’s fish and seafood are produced by aquaculture, which is one of the biggest contributors to the world’s food security. The substantial increase in prices of conventional feed ingredients and the over-exploitation of natural resources are some of the biggest constraints to aquaculture production. To overcome this stress, different approaches and techniques are used, among which the use of non-conventional feed ingredients in the aquaculture sector is the most recent approach. Different non-conventional feed ingredients such as plant-based products, algae (both micro and macroalgae), single-cell protein (bacteria and yeast), and insect meal are currently used in aquaculture for sustainable food production. Amongst all these novel ingredients, insects have greater potential to replace fishmeal. The existence of about 1.3 billion tons of food and agriculture waste from the food chain supply poses a serious environmental threat. Insects are tiny creatures that can thrive on organic waste and thus can convert the waste to wealth by the bioconversion and nutritional upcycling of organic waste. Insects have the potential to recover nutrients from waste aquaculture products, and many fish species feed on insects naturally. Therefore, employing insects in the aquaculture sector to replace fishmeal is an eco-friendly approach. The present review briefly highlights emerging non-conventional feed ingredients, with special attention given to insects. The current review also focuses on the nutritional value of insects, factors affecting the nutritional value of insects, potential insects that can be employed in the aquaculture sector, the physiological response of fish when fed with insect meal, techno-functional properties of insect meal, and emerging approaches for addressing possible downsides of employing insect meal in fish diets. Finally, it suggests avenues for further research into these inventive fishmeal replacements.

In Silico Dissection and Expression Analysis of Sucrose Synthase Gene Family in Sugarcane - Muhammad Noman; Iqra Siddique; Bilal Saleem; Saiqa Ilyas; Shaukat Ali; Muhammad Ramzan Khan (Sugar Tech, 2022)

Recent trends in green synthesis of silver, gold, and zinc oxide nanoparticles and their application in nanosciences and toxicity: a review - Muhammad Musaddiq Shah; Khurshid Ahmad; Bashir Ahmad; Shahid Masood Shah; Hamid Masood; Muhammad Aamir Ramzan Siddique; Rasheed Ahmad (Nanotechnology for Environmental Engineering, 2022)

Occurrence of shallow landslides triggered by increased hydraulic conductivity due to tree roots - Mingyue Qin; Peng Cui; Yao Jiang; Jian Guo; Guotao Zhang; Muhammad Ramzan (Landslides, 2022)

A static and dynamic copula-based ARIMA-fGARCH approach to determinants of carbon dioxide emissions in Argentina - Sel Ly; Salman Sarwat; Wing-Keung Wong; Muhammad Ramzan; Hung D. Nguyen (Environmental Science and Pollution Research, 2022)

Review on integrated disease and pest management of field crops - Muneer Abbas; Muhammad Saleem; Dilbar Hussain; Muhammad Ramzan; Muhammad Jawad Saleem; Sohail Abbas; Niaz Hussain; Muhammad Irshad; Khalid Hussain; Ghulam Ghouse; Mudassar Khaliq; Zubeda Parveen (International Journal of Tropical Insect Science, 2022)

Appraisal of CO2 emission in Tunisia’s industrial sector: a dynamic vector autoregression method - Besma Talbi; Muhammad Ramzan; Hafiz Arslan Iqbal; Buhari Doğan (Environmental Science and Pollution Research, 2022)

Correction to: Fabrication, Evaluation, In Vivo Pharmacokinetic and Toxicological Analysis of pH-Sensitive Eudragit S-100-Coated Hydrogel Beads: a Promising Strategy for Colon Targeting - Sadia Rehman; Nazar Muhammad Ranjha; Hina Shoukat; Asadullah Madni; Faiz Ahmad; M. Rafi Raza; Qazi Adnan Jameel; Abdul Majeed; Nasreen Ramzan (AAPS PharmSciTech, 2022)

Environmental pollution and agricultural productivity in Pakistan: new insights from ARDL and wavelet coherence approaches - Muhammad Ramzan; Hafiz Arslan Iqbal; Muhammad Usman; Ilhan Ozturk (Environmental Science and Pollution Research, 2022)

Identification of putative genetic variants in major depressive disorder patients in Pakistan - Sarah Rizwan Qazi; Muhammad Irfan; Zoobia Ramzan; Muhammad Jahanzaib; Maleeha Zaman Khan; Mahrukh Nasir; Muhammad Shakeel; Ishtiaq Ahmad Khan (Molecular Biology Reports, 2022)

RNA interference-mediated knockdown of odorant-binding protein 2 and MP58 gene causes mortality in Myzus persicae - Iqra Mahmood; Amber Afroz; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Umer Rashid; Muhammad Azmat Ullah Khan; Naeem Mehmood Ashraf; Sadia Alam (International Journal of Tropical Insect Science, 2022)

Intron-containing hairpin RNA interference vector for OBP8 show promising mortality in peach potato aphid - Amber Afroz; Safeena Aslam; Umer Rashid; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Muhammad Qasim Shahzad But; Sabaz Ali Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Inducible knockdown of Mycobacterium smegmatis MSMEG_2975 (glyoxalase II) affected bacterial growth, antibiotic susceptibility, biofilm, and transcriptome - Muhammad Haris; Changming Chen; Jing Wu; Muhammad Noman Ramzan; Ayaz Taj; Shanshan Sha; Hayan Ullah; Yufang Ma (Archives of Microbiology, 2022)

RETRACTED ARTICLE: COVID-19 and stock exchange return variation: empirical evidences from econometric estimation - Yousaf Latif; Ge Shunqi; Shahid Bashir; Wasim Iqbal; Salman Ali; Muhammad Ramzan (Environmental Science and Pollution Research, 2021)

The environmental sustainability effects of financial development and urbanization in Latin American countries - Tomiwa Sunday Adebayo; Muhammad Ramzan; Hafiz Arslan Iqbal; Abraham Ayobamiji Awosusi; Gbenga Daniel Akinsola (Environmental Science and Pollution Research, 2021)

Evaluation of sex steroid hormones and reproductive irregularities in diethyl phthalate-exposed premature mice: modulatory effect of raw honey against potential anomalies - Chaman Ara; Asmatullah; Faiza Yaseen; Shaukat Ali; Hafiz Abdullah Shakir; Muhammad Khan; Shagufta Andleeb; Nageena Ramzan (Environmental Science and Pollution Research, 2021)

Environmental quality: examining role of financial development, institutional capacity, and corruption - Ameet Kumar; Muhammad Ramzan Kalhoro; Rakesh Kumar; Niaz Ahmed Bhutto; Ruqia Shaikh (Environmental Science and Pollution Research, 2021)

Physiopathology and effectiveness of therapeutic vaccines against human papillomavirus - Noor Ayesha; Sara Aboulaghras; Muhammad Jahangeer; Areej Riasat; Rehana Ramzan; Rameen Fatima; Muhammad Akram; Abdelaali Balahbib; Abdelhakim Bouyahya; Ekaterina Sepiashvili; Gokhan Zengin; Mohammad Ali Shariati (Environmental Science and Pollution Research, 2021)

Catalytic transformation of Brassica nigra oil into biodiesel using in-house engineered green catalyst: Development and characterization - Ushna Fatima; Farooq Ahmad; Muhammad Ramzan; Saba Aziz; Muhammad Tariq; Hafiz M. N. Iqbal; Muhammad Imran (Clean Technologies and Environmental Policy, 2021)

Fabrication, Evaluation, In Vivo Pharmacokinetic and Toxicological Analysis of pH-Sensitive Eudragit S-100-Coated Hydrogel Beads: a Promising Strategy for Colon Targeting - Sadia Rehman; Nazar Muhammad Ranjha; Hina Shoukat; Asadullah Madni; Faiz Ahmad; M. Rafi Raza; Qazi Adnan Jameel; Abdul Majeed; Nasreen Ramzan (AAPS PharmSciTech, 2021)

Screening of different legumes for the developmental preference of Callosobruchus maculatus (Bruchidae: Coleoptera) - Muhammad Shahid Nisar; Ikram Ul Haq; Hassan Ramzan; Dalal M. Aljedani; Muhammad Qasim; Waqar Islam; Khalid Ali Khan (International Journal of Tropical Insect Science, 2021)

Genome-wide characterization and expression analysis of pseudo-response regulator gene family in wheat - Aliya Errum; Nazia Rehman; Muhammad Ramzan Khan; Ghulam Muhammad Ali (Molecular Biology Reports, 2021)

Histomorphology of Seminal Vesicles Subsequent to Exogenous Neurokinin B Administration in New Zealand White Rabbits - Zain Ullah; Muhammad Haris Ramzan; Faiqah Ramzan (International Journal of Peptide Research and Therapeutics, 2020)

Assessment of European and hybrid aspen clones efficiency based on height growth and removal percentage of petroleum hydrocarbons—a field trial - Mir Md Abdus Salam; Muhammad Mohsin; Fahad Rasheed; Muhammad Ramzan; Zikria Zafar; Pertti Pulkkinen (Environmental Science and Pollution Research, 2020)
Soils polluted by organic or inorganic pollutants are an emerging global environmental issue due to their toxic effects. A phytoremediation experiment was conducted to evaluate the extraction potential of three European aspen clones (R2, R3, and R4) and seven hybrid aspen clones (14, 27, 34, 134, 172, 191, and 291) grown in soils polluted with hydrocarbons (includes polycyclic aromatic hydrocarbons (PAH) and total petroleum hydrocarbons (TPH)). Height growth, plant survival rates, and .hydrocarbon removal efficiencies were investigated over a 4-year period at a site in Somerharju, Luumaki Finland, to assess the remediation potential of the clones. Hydrocarbon content in the soil was determined by gas chromatography and mass spectrometry. The results revealed that hybrid aspen clones 14 and 34 and European aspen clone R3 achieved greater height growth (171, 171, and 114 cm, respectively) than the other clones in the study. Further, the greatest removals of PAH (90% at depth 10–50 cm) and (86% at depth 5–10 cm) were observed in plot G15 planted with clone R2. Furthermore, the greatest TPH removal rate at 5–10 cm depth (C 22 –C 40 , 97%; C 10 –C 40 , 96%; and C 10 –C 21 , 90%) was observed in plot 117 with clone 134. However, other clones demonstrated an ability to grow in soils with elevated levels of TPH and PAH, which indicates their tolerance to hydrocarbons and their potential capacity for phytoremediation of hydrocarbon-polluted soils. Our study suggests that European aspen and hybrid aspen clones could be used for the remediation of soils polluted with PAH and TPH.

Exogenous Neurokinin B Administration May Have a Strong Effect on Negative Feedback Loop of Hypothalamic Pituitary Thyroid Axis - Maria Wishal Asmat; Muhammad Haris Ramzan; Faiqah Ramzan (International Journal of Peptide Research and Therapeutics, 2020)

Biofortification with Zinc and Iron Improves the Grain Quality and Yield of Wheat Crop - Yasir Ramzan; Muhammad Bilal Hafeez; Shahbaz Khan; Majid Nadeem; Saleem-ur-Rahman; Sumaira Batool; Javed Ahmad (International Journal of Plant Production, 2020)

The bacterial RNA ligase RtcB accelerates the repair process of fragmented rRNA upon releasing the antibiotic stress - Muhammad Ramzan Manwar; Changjun Shao; Xing Shi; Jian Wang; Qiang Lin; Yigang Tong; Yu Kang; Jun Yu (Science China Life Sciences, 2020)

Improved transdermal delivery of cetirizine hydrochloride using polymeric microneedles - Muhammad Sohail Arshad; Sana Hassan; Amjad Hussain; Nasir Abbas; Israfil Kucuk; Kazem Nazari; Radeyah Ali; Suleman Ramzan; Ali Alqahtani; Eleftherios G. Andriotis; Dimitris G. Fatouros; Ming-Wei Chang; et al. (DARU Journal of Pharmaceutical Sciences, 2019)

Homotypic Clusters of Transcription Factor Binding Sites in the First Large Intron of AGL24 MADS-Box Transcription Factor Are Recruited in the Enhancement of Floral Expression - Tajammul Hussain; Nazia Rehman; Safeena Inam; Wajya Ajmal; Amber Afroz; Aish Muhammad; Yusuf Zafar; Ghulam Muhammad Ali; Muhammad Ramzan Khan (Plant Molecular Biology Reporter, 2019)

Antiplatelet activity, molecular docking and QSAR study of novel N′-arylmethylidene-3-methyl-1-phenyl-6-p-chlorophenyl-1H-pyrazolo[3,4-b] pyridine-4-carbohydrazides - Ayesha Ramzan; Sara Siddiqui; Ahmad Irfan; Abdullah G. Al-Sehemi; Aftab Ahmad; Francis Verpoort; Adeel H. Chughtai; Misbahul A. Khan; Munawar A. Munawar; Muhammad Asim Raza Basra (Medicinal Chemistry Research, 2018)

Comparison of total ozone column observations from space-borne Ozone Monitoring Instrument with ground-based Dobson Ozone Spectrophotometer measurements at an urban location in Indo-Gangetic Basin - Zia Ul-Haq; Zertasha Ramzan; Salman Tariq; Syeda Adila Batool; Muhammad Ali; Javed Sami (International Journal of Remote Sensing, 2018)

High-resolution regional gravity field model of Pakistan based on best residual terrain model (RTM) of topography and interpolation techniques - Muhammad Sadiq; Aneeque A. Qazi; M. Ramzan (Arabian Journal of Geosciences, 2017)

WsMAGO2, a duplicated MAGO NASHI protein with fertility attributes interacts with MPF2-like MADS-box proteins - Humera Ihsan; Muhammad Ramzan Khan; Wajya Ajmal; Ghulam Muhammad Ali (Planta, 2015)

Pre-planting exogenous application of gibberellic acid influences sprouting, vegetative growth, flowering, and subsequent bulb characteristics of ‘Ad-Rem’ tulip - Fahad Ramzan; Adnan Younis; Atif Riaz; Sajid Ali; Muhammad Irfan Siddique; Ki-Byung Lim (Horticulture, Environment, and Biotechnology, 2014)

Characterization of Reactive Red-120 Decolorizing Bacterial Strain Acinetobacter junii FA10 Capable of Simultaneous Removal of Azo Dyes and Hexavalent Chromium - Faiza Anwar; Sabir Hussain; Shahla Ramzan; Farhan Hafeez; Muhammad Arshad; Muhammad Imran; Zahid Maqbool; Naila Abbas (Water, Air, & Soil Pollution, 2014)

Functional evolution of cis-regulatory modules of STMADS11 superclade MADS-box genes - Muhammad Ramzan Khan; Ghulam Muhammad Ali (Plant Molecular Biology, 2013)

Divergences of MPF2-like MADS-domain proteins have an association with the evolution of the inflated calyx syndrome within Solanaceae - Jisi Zhang; Muhammad Ramzan Khan; Ying Tian; Zhichao Li; Simone Riss; Chaoying He (Planta, 2012)

The MADS-domain protein MPF1 of Physalis floridana controls plant architecture, seed development and flowering time - Chaoying He; Ying Tian; Rainer Saedler; Nadia Efremova; Simone Riss; Muhammad Ramzan Khan; Alexander Yephremov; Heinz Saedler (Planta, 2010)

Seroprevalence of Toxoplasma gondii in sheep and goats in Rahim Yar Khan (Punjab), Pakistan - M. Ramzan; M. Akhtar; F. Muhammad; I. Hussain; E. Hiszczyńska-Sawicka; A. U. Haq; M. S. Mahmood; M. A. Hafeez (Tropical Animal Health and Production, 2009)

High frequency shoot regeneration and Agrobacterium-mediated DNA transfer in Canola (Brassica napus) - Muhammad Ramzan Khan; Hamid Rashid; Muhammad Ansar; Zubeda Chaudry (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)